Diagnosis, Management, and Histopathological Characteristics of Corneal Keloid: A Case Series and Literature Review. Issue 5 (September 2016) - Gupta, Jaya; Gantyala, Shiva Prasad; Kashyap, Seema; Tandon, Radhika
Abstract : Purpose: Corneal keloids are rare lesions that develop in cases of corneal insult. We describe the clinical features, subsequent management, and histopathological characteristics of 5 of our cases of corneal keloid. Design: This was an interventional case series. Methods: A total of 5 patients were examined and treated for corneal keloid. Results: Five Indian patients with no keloids on the skin or any history of hypertrophic scar formation complained of progressive painless dimness of vision and a slowly growing epicorneal mass. There was a history of traumatic cataract extraction with anterior chamber intraocular lens implantation in 2 of the cases, corneal decompensation after viral keratouveitis in the third case, a history of penetrating injury in the fourth, and a history of anterior stromal puncture for bullous keratopathy in the last case. On examination, a pearly white glistening mass occupying almost the entire cornea was seen in all. Treatment options considered were superficial keratectomy with amniotic membrane transplantation and lamellar and penetrating keratoplasty. Histopathological features in all patients were consistent with a diagnosis of corneal keloid. Immunohistochemical stain was positive for vimentin. Conclusions: Corneal keloid should be suspected in cases of enlarging white glistening corneal scar after trauma. Although unusual, it can also appear after corneal infections that serve as persistent stimuli to the repair process. Management options are varied as outlined previously.